The Authority Concept among University students of Baghdad - ايمان صادق عبد الكريم سوسن حسن غالي (College of Education for Women, 2019)
The Present study aims to shed some light on the concept of authority of university students and to find statistically significant differences as regards this concepts in accordance with three variables gender (males, females),field of study(scientific ,humanities)and grade(second ,fourth). To accomplish the study a ( 7) level scale was developed for the concept of authority and it subjected to validity and credibility the scale was used with 590 student sample (237) males and (353) females Results show that male students show obedience to authority forms below the Avery e component with the theoretical Avery of the scale besides ,reinforcement was on the top of authority chain ,followed by person traits ,friends, affect punishment and traditional authority knowledge authority, Was the last addition ,there were no statistically significant difference concerning gender ,field of study and grade.